ANALISIS DE LA RELACION QUE EXISTE ENTRE EL PLAN CURRICULAR Y EL PERFIL DEL EGRESADO DE LAL CARRERA DE LABORATORIO PEDAGOGICO DE LA UNIVERSIDAD TECNICA DE BABAHOYO, LINEAMIENTOS ALTERNATIVOS - FRANKLIN CHIPPE VILLAMAR (2004)
ANALYSIS OF THE RELATIONSHIP THAT EXISTS BETWEEN THE CURRICULUM PLAN AND THE PROFILE OF THE GRADUATE OF THE PEDAGOGICAL LABORATORY COURSE OF THE TECHNICAL UNIVERSITY OF BABAHOYO, ALTERNATIVE GUIDELINES